Association of Physical Activity and Nutritional Status with Blood Glucose Levels Among Patients of Diabetes Mellitus Type 2 at Puskesmas Sei Langkai Kota Batam - Novianti, Tri Utami; Herviana, Herviana; Pratiwi, Siska (Journal of Global Nutrition, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia due to inadequate insulin production or impaired insulin utilization. In Indonesia, the prevalence of DM reaches 11.7% in adults, with a significant burden in Batam, particularly at Puskesmas Sei Langkai. This study aims to determine the relationship between physical activity and nutritional status with blood glucose levels in type 2 DM patients aged 45–69 years. This is an observational analytical study with a cross-sectional design conducted in October 2025, involving 120 respondents selected purposively. Physical activity was measured using a short IPAQ questionnaire and converted to MET-minutes/week, nutritional status was measured using Body Mass Index (BMI), and random blood glucose levels were measured using a glucometer. Data analysis was performed using the Spearman correlation test. The results showed that the majority of respondents were aged 45–59 years (76.7%), female (70.8%), had a high school education (65.8%), were unemployed (67.5%), and had suffered from DM for 1–5 years (62.5%). Most had moderate physical activity (65.8%) and normal nutritional status (77.5%), but 53.3% had uncontrolled blood glucose levels. Analysis showed a significant negative relationship between physical activity and blood glucose levels (r = -0.305, p = 0.001), while nutritional status showed no significant relationship (r = 0.159, p = 0.083). These findings confirm that physical activity plays an important role in blood glucose control, while nutritional status alone is not the main determining factor. DM management should include regular physical activity, a balanced diet, adherence to therapy, and routine glucose monitoring.